Vernakularisasi Tafsir Al-Qur’an di Kalimantan Barat (Studi Atas Tafsir Ᾱyāt aṣ-Ṣiyām Karya Muhammad Basiuni Imran) - Wendi Parwanto (SUHUF, 2022)
This study examines the vernacularization of tafsir Ᾱyāt aṣ-Ṣiyām by M. Basiuni Imran which has not been done by many researchers. This type of research is library research with the primary data of manuscript tafsir Ᾱyāt aṣ-Ṣiyām by M. Basiuni Imran. The analytical model used is a narrative analysis and by using the concept of vernacularization. The conclusion of this article shows that vernacularization is not only a process of translating from Arabic to a local language but there are elements of locality that are accommodated in the translation process. The form of vernacularization is divided into two, namely: 1) vernacularization in the form of diction and language; 2) vernacularization in the form of narrative or interpretation content. Likewise in the tafsir Ᾱyāt aṣ-Ṣiyām , the form of vernacularization in the interpretation belongs to the vernacularization of diction or language, namely the use of the words Uwas (remember), Tembawang (a former farming hut), and Sungai (a description of the reality of West Kalimantan).